2014
DOI: 10.1177/0898264314526619
|View full text |Cite
|
Sign up to set email alerts
|

Change in Balance Confidence and Its Associations With Increasing Disability in Older Community-Dwelling Women at Risk for Falling

Abstract: Objectives To describe change in balance confidence, and to identify associated factors and disabling consequences. Method Secondary analysis of 2 years of data collected from 272 older women enrolled in a randomized clinical trial of fall prevention. Balance confidence and disability measures were assessed at baseline, after the 12 week intervention, and at 1 and 2 years follow-up. Associated factors were measured at baseline. Results Balance confidence varied at baseline and decreased 5% over 2 years, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…This analysis was chosen to illustrate the statistical use of the FWF in SPRE for fall prevention in older adults because little statistical analytical work has been published which looks at prevalence and incidence of adults with fof together with those who have fallen. Even if, as Talley, et al (2014) suggested, fear of falling and having a fall are separate constructs, they can both be considered at the same time like fruit in a bowl by using FWF. This concept was first presented at the Joint Statistical Meeting by Weissman-Miller & Graham (2014).…”
Section: Pilot Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…This analysis was chosen to illustrate the statistical use of the FWF in SPRE for fall prevention in older adults because little statistical analytical work has been published which looks at prevalence and incidence of adults with fof together with those who have fallen. Even if, as Talley, et al (2014) suggested, fear of falling and having a fall are separate constructs, they can both be considered at the same time like fruit in a bowl by using FWF. This concept was first presented at the Joint Statistical Meeting by Weissman-Miller & Graham (2014).…”
Section: Pilot Studiesmentioning
confidence: 99%
“…Though prevalence of fof varied greatly due to measure variablity, a systemic review identified major fof risk factors as having a fall, being female, and aging adults (Scheffer, Schuurmans, van Dijk, van der Hooft, & de Rooij, 2008). Consequences of fof have been identified as falls, decreased fall-related self efficacy, and activity restriction/decreased quality of life (Jørstad et al, 2005;Scheffer et al, 2008;Talley, Wyman, Gross, Lindquist, & Gaugler, 2014;Tinetti et al, 1994;Tinetti, Richman, & Powell, 1990). As a result of its negative influence and impact on falls and function in older adults, those with fof should be addressed within fall prevention programming.…”
Section: Introduce the Problemmentioning
confidence: 99%
See 3 more Smart Citations